Software Architecture Hour : Building Evolutionary Architectures with Rebecca Parsons (O'Reilly Media, Inc., 2022)
How is long-term planning possible when everything changes all the time--and how do you address the unfortunate fact that architectures often gradually degrade? Evolutionary architectures support the building of systems that allow architects and developers to make sweeping changes to the most important parts with confidence. Join us for a special conversation on evolutionary architectures with Neal Ford and Thoughtworks CTO Rebecca Parsons. They'll discuss how their ideas around evolutionary architectures have evolved since the publication of their 2017 book Building Evolutionary Architectures (cowritten with Patrick Kua). Learn practices that allow developers to build continual architectures, which evolve cleanly without the need for a crystal ball. This is a chance for you to learn about architecture and Neal and Rebecca's own career journeys. They'll spend a few minutes covering the trends that are influencing architecture, then tell you what you need to know to stay ahead of the curve. What you'll learn and how you can apply it Understand what evolutionary architectures are and how to implement them See what's coming next with software architecture This live event is for you because... You want to learn more about building and maintaining evolutionary architectures. You're looking for ways to improve your architecture. Recommended follow-up: Read Building Evolutionary Architectures (book) Read Software Architecture Metrics (book) Read Fundamentals of Software Architecture (book) Read Software Architecture: The Hard Parts (book) Explore Evolutionary Architectures Fundamentals (course) Attend Software Architecture Superstream: Architecture Meets Data (live online event on November 30, 2022).